The Relationship between Energy Consumption (Renewable Energy), Economic Growth and Agro-Industrial Complex in Kazakhstan - Sartbayeva, Gulbakhram; Balapanova, Elmira; Mamytkanov, Darkhan Kozhanovich; Talimova, Lyazat; Lukhmanova, Gulnar; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2023)
This study analyzes the relationship between energy consumption (renewable energy), economic growth, and developments in Kazakhstan’s agricultural industry complex (agriculture and livestock outputs) between 1991 and 2021 and the interaction of these factors. Analysis data were retrieved from the databases of Our World in Data, the World Bank, and the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan. The study examines energy consumption over two variables. The first is the share of energy obtained from renewable energy sources in the total energy consumption, and the second is the total energy consumption. It is only natural to expect an increase in agricultural production due to new technologies in the industry. However, it is also essential to examine whether the country’s economic growth, agricultural fields, and employment in agriculture play a role in energy consumption. One of the significant indicators of the developments in the agricultural industry is the reflection of the production in agriculture and animal husbandry on internationally valid indices. Therefore we deemed it appropriate to compare the input variables with the food index produced by the World Bank. The effects of agricultural industry assets and agricultural developments on energy consumption were examined using the hierarchical regression analysis approach. The findings showed that agricultural developments affect energy consumption, especially renewable energy consumption. This study concludes that it is necessary to examine the causality of this effect and whether it transforms into a short-term or long-term effect.